Ca/Alq3 hybrid cathode buffer layer for the optimization of organic solar cells based on a planar heterojunction. (November 2016) - El Jouad, Z.; Barkat, L.; Stephant, N.; Cattin, L.; Hamzaoui, N.; Khelil, A.; Ghamnia, M.; Addou, M.; Morsli, M.; Béchu, S.; Cabanetos, C.; Richard-Plouet, M.; et al.
Abstract: Use of efficient anode cathode buffer layer (CBL) is crucial to improve the efficiency of organic photovoltaic cells. Here we show that using a double CBL, Ca/Alq3, allows improving significantly cell performances. The insertion of Ca layer facilitates electron harvesting and blocks hole collection, leading to improved charge selectivity and reduced leakage current, whereas Alq3 blocks excitons. After optimisation of this Ca/Alq3 CBL using CuPc as electron donor, it is shown that it is also efficient when SubPc is substituted to CuPc in the cells. In that case we show that the morphology of the SubPc layer, and therefore the efficiency of the cells, strongly depends on the deposition rate of the SubPc film. It is necessary to deposit slowly (0.02 nm/s) the SubPc films because at higher deposition rate (0.06 nm/s) the films are porous, which induces leakage currents and deterioration of the cell performances. The SubPc layers whose formations are kinetically driven at low deposition rates are more uniform, whereas those deposited faster exhibit high densities of pinholes. Graphical abstract: Highlights: Use of a double cathode buffer layer Ca (3 nm)/Alq3 (6 nm) in Inverted organic solar cells. Improvement of performances of Inverted organic solar cells using this cathode structure. Highlighting the strong influence of the deposition rate on the morphology of SubPc layers High reproducibility of cells performance when homogeneous SubPc film is used.